Analisis Strategi Pengembangan Usaha Mikro Menengah (UMKM) Menggunakan Sistem E-Commerce Dengan Model Content Marketing Pada Coffe Shop Kopang Kota Tebing Tinggi - Sri Devi Hariani; Rapat Piter Sony; Imelda Mardayanti; Restu A Suryaman (Digital Business Progress, 2023)
This study aims to determine the content marketing strategy in the development of micro, small and medium enterprises (MSMEs) at Coffee Shop Kopang, Tebing Tinggi City. The researcher used a descriptive qualitative approach. This qualitative research consists of disclosing facts, phenomena, variables and circumstances that occurred when the research was in progress and presenting what was happening. Qualitative descriptive research interprets and describes data on the current situation, attitudes and opinions that occur in society, contradictions of two or more, relationships between variables, differences in facts, influence on a condition and others. Qualitative method is a research method based on the philosophy of postpositivism, used to examine the state of nature. The results of this study are digital marketing strategies while still following the concept of marketing strategies to develop products and business competitiveness in the market. In addition, digital marketing strategies to increase the competitiveness of MSME products include segmentation that focuses on products and prices as well as quality on consumer buying interest. In addition, word of mouth conveyed by customers to influence others has a very significant impact.